Evaluation of Anti-Tank Guided Missiles: An integrated Fuzzy Entropy and Fuzzy CoCoSo multi criteria methodology using technical and simulation data - Erdal, Hamit; Kurtay, Kemal Gurol; Dagistanli, Hakan Ayhan; Altundas, Aygun (Applied soft computing, 2023)
The Anti-Tank Guided Missiles (ATGMs) selection problem, a sub-problem of the Weapon Systems Selection Problems (WSSP), is an extremely important strategical level decision problem and is the main focus of this study. The study aims to determine a new methodology that represents accurate and reliable results from simulation model. This model decides on the anti-tank weapon system for various combat scenarios with high uncertainty. Data obtained from hundreds of simulation scenarios, with different combat conditions such as friendly and enemy forces, terrain, and environmental conditions, and technical weapon specifications is used to define solutions for the ATGM problem, such a solution proposal was not seen in any of the previous studies. For this aim, we proposed a comprehensive methodology consisting of 4 phases and 15 steps, using simulation and technical data, Fuzzy Shannon’s Entropy (F-Entropy) based on α-level sets, and Fuzzy CoCoSo with Bonferroni (F-CoCoSo’B) methods for the selection of ATGMs to be used in the close quarter combat conditions. F-Entropy method is utilized for obtaining the criteria weights and F-CoCoSo’B is used for ranking the ATGM alternatives. 3 main and 22 sub-criteria have been determined by considering not only the technical data of the weapon systems but also data obtained from JCATS simulation tool. This combination of data sources results in criteria that reflects the combat environment more precisely, when compared to previous studies where only technical data or the experience of military experts were collected. The sensitivity analysis performed to test the validity and applicability of the proposed methodology approves the stability, robustness, and practicality of the methodology. The purpose of this paper is to present the proposed methodology, findings, and insights. •We proposed a comprehensive methodology consisting of 4 phases and 15 steps for weapon systems selection problem (WSSP).•The decision criteria are determined quite comprehensive with 3 main and 22 sub-criteria consisting simulation and technical data.•Relatively recent and powerful methods, F-Entropy based on α-level sets and F-CoCoSo’B, are firstly utilized for a WSSP in general and for an ATGMs selection problem in particular.•The proposed enhanced fuzzy MCDM methodology, makes it possible to evaluate alternatives in spite of uncertainties and a lack of quantitative information, and enables a more flexible decision-making process, is considered a powerful managerial tool for any WSSP.